Assessing Work System Processes Using Macroergonomic Analysis and Design Approach: A Literature Review - Fadhilah, Nahdah; Abdul Rahim Matondang; Anizar Anizar (Jurnal Sistem Teknik Industri, 2024)
This study's goal is to provide an overview of the macroergonomics approach, which is used to evaluate work systems and make improvements to working conditions and efficiency. A process for the system evaluation was developed using the pertinent framework, Macroergonomic Analysis and Design (MEAD). Using the MEAD framework, the system may be assessed more completely overall, and any conflicts can be resolved to fully harmonize the system. A thematic analysis of papers addressing macroergonomic analysis and design (MEAD) is the methodology used in this study. To successfully complete a research project using this methodology, ten steps must be followed. The ten steps are as follows: examining the subsystem of organizational and environmental design; identifying the type of manufacturing system and establishing performance benchmarks; outlining work procedures and unit operations; detecting variances; generating the matrix of variances; establishing the role network and key variance control table; allocating functions and designing jointly; recognizing the views of roles and responsibilities; creating and modifying interfaces and supporting subsystems; putting into practice, refining, and upgrading.